Towards a theory of praxis in public administration meeting current challenges of redemocratization in the Philippines - Tancangco, Luzviminda (Philippine Journal of Public Administration, 1988)
The paper explores the meaning of creative praxis, the transformative link between theory and practice, and its prospects for a conservative discipline like Public Administration. This was done through the aid of secondary data and information and actual experiences gathered in connection with the elections study series (the 1984, 1986, 1987-1988 Elections Project) conducted by the UP-CPA Research Team. The study reveals new areas for future exploration with creative praxis as a potentially powerful tool for analysis and guide to action.